1992
DOI: 10.1139/v92-217
|View full text |Cite
|
Sign up to set email alerts
|

Chiral organosilicon compounds in synthesis. Preparation and stereoselective alkylations of silylcinnamyl carbanions

Abstract: Silylallyl carbanions of type 13 bearing a chiral lithium complexing substituent remote from silicon can be alkylated regio- and stereoselectively at the α-position by small electrophiles in nonpolar solvents. The regiochemical outcome of the reaction was found to be highly dependent on the size of the incoming electrophile. Secondary alkyl halides react preferentially at the γ-center and good levels of stereoselectivity are still obtained in nonpolar solvents despite the rather long distance between the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Exactly the same outcome was observed in the quenching of 9 with Me 3 SiCl in thf, indicating the position of the lithium cation relative to the pentadienyl carbons does not influence the reaction to any significant extent. The most probable explanation for the reaction taking place at the ε-carbon is that steric effects dominate, which is consistent with Chan’s study on related lithium allylsilanes …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Exactly the same outcome was observed in the quenching of 9 with Me 3 SiCl in thf, indicating the position of the lithium cation relative to the pentadienyl carbons does not influence the reaction to any significant extent. The most probable explanation for the reaction taking place at the ε-carbon is that steric effects dominate, which is consistent with Chan’s study on related lithium allylsilanes …”
Section: Resultssupporting
confidence: 88%
“…In the context of C–H functionalization, allylsilanes bear some similarities to aromatic molecules owing to the presence of more than one reactive site, i.e., α or γ relative to silicon, and the broad synthetic applications of allylsilanes render the issue of regioselective functionalization of lithiated allylsilanes one of considerable importance . Chan et al have demonstrated that allylsilanes with aminoalkyl groups built into the silyl substituent can be lithiated with s BuLi and subsequently functionalized in a selective manner . Electrophilic quenching of the Lewis-base-functionalized allyl-lithium compounds by alkyl halides showed good selectivity for the α-position with small alkyl halides (e.g., methyl iodide), but bulkier electrophiles (e.g., isopropyl iodide) reacted preferentially at the γ-position.…”
Section: Introductionmentioning
confidence: 99%
“…A similar level of control was found for the allylsilane 1916 962 and the propargylsilane 1918 963 carrying the same proline-derived auxiliary, and which gave the allylic and propargylic alcohols 1917 and 1919, respectively (Scheme 461).…”
Section: Vinylsilanessupporting
confidence: 58%
“…Silylallyl carbanions 463 bearing a chiral lithium complexing substituent remote from silicon are similarly α-alkylated by small electrophiles in nonpolar solvents to give 464 and γ-attacked by secondary halides to form 465 . Both types of reaction proceed stereoselectively (Scheme ) 81 …”
Section: Functionalized Allyltrialkylsilanes (Cc−c−sir3)mentioning
confidence: 99%
“…Both types of reaction proceed stereoselectively (Scheme 81). 258 The reactions of aminomethyl-substituted silylallyl anions with carbonyl compounds give a mixture of the Rand γ-products whereby the γ-selectivity is increased with the decrease of the steric bulkiness of the amino group. If the silyl moiety in 466 contains a group L which is capable of internal chelation (467), the reactions with carbonyl compounds give preferentially γ-addition products such as 468 and 469 (Scheme 82) analogous to allyltrialkylsilanes.…”
Section: Functionalized Allyltrialkylsilanes (Cdc−c−sir 3 )mentioning
confidence: 99%